2007
DOI: 10.1110/ps.062469507
|View full text |Cite
|
Sign up to set email alerts
|

Loop anchor modification causes the population of an alternative native state in an SH3‐like domain

Abstract: Many stably folded proteins are proposed to contain long, unstructured loops. A series of hybrid proteins (EbE1-4) containing the folded scaffold of photosystem I accessory protein E (PsaE), an SH3-like protein, and the 40-residue heme-binding loop of cytochrome b 5 was created to inspect the dependence of thermodynamic and kinetic parameters on the residues at the interface of folded and flexible regions. Compared to the simplest hybrid (EbE1), the chimeras differed by Gly insertions (EbE2, EbE3) or an asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…18,19 The influence of the heme binding loop on its supporting scaffold has been investigated by substitution for a flexible loop in photosystem I accessory protein E (PsaE). 19,20 Chemical and thermal denaturation of the chimeric proteins suggests that the thermodynamic cost of closing the H2-H5 loop in apocyt b 5 need not be high. The presence of residual structure in H2 and elsewhere may explain values lower than the Gaussian estimate.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The influence of the heme binding loop on its supporting scaffold has been investigated by substitution for a flexible loop in photosystem I accessory protein E (PsaE). 19,20 Chemical and thermal denaturation of the chimeric proteins suggests that the thermodynamic cost of closing the H2-H5 loop in apocyt b 5 need not be high. The presence of residual structure in H2 and elsewhere may explain values lower than the Gaussian estimate.…”
Section: Introductionmentioning
confidence: 99%
“…In prior work, chimeric constructs consisting of the cyt b 5 heme binding loop (*40 residues encompassing H2-H3-b5-H4-H5) grafted onto an alternate scaffold protein, an SH3-like domain, were prepared to establish the free energy penalty of carrying this particular intrinsically disordered region. 12,13 With a family of four closely related chimeras and their denaturation behavior, it was found that the energetic cost depended strongly on the way in which the loop-scaffold interface was designed. The four chimeras did not bind heme specifically and emphasized the importance of correctly configuring the chain trajectory from and back into the folded scaffold.…”
Section: Introductionmentioning
confidence: 99%